Unemployment risk-sharing in the EU: How policy design influences citizen support for European unemployment policy. (June 2022) - Burgoon, Brian; Kuhn, Theresa; Nicoli, Francesco; Vandenbroucke, Frank
This article explores public preferences for European unemployment programs explicitly discussed in actual policymaker debate. European policymakers have been considering European-level Unemployment Risk Sharing (EURS) to stabilize member-state economies and provide a safety net for the unemployed. Using a conjoint experiment conducted in 13 European member states, we analyze public support across six crucial policy dimensions of EURS. The findings reveal that (a) overall support for EURS policies is broad and substantial, but sensitive to particular policy mixes; (b) citizen support is conditional on the program being generous and on coverage being limited to countries providing education and training and individual beneficiaries looking for and accepting work; and (c) cross-country variation is modest and most prominent with respect to cross-country redistribution.